Thoracoscopic repair of esophageal atresia: Comparison with open approach - Chun-Hui Lin; Yih-Cherng Duh; Yu-Wei Fu; Yao-Jen Hsu; Chin-Hung Wei (Formosan Journal of Surgery, 2018)
Background: The aim of the present study is to evaluate our initial experiences of thoracoscopic repair (TR) for esophageal atresia with/without trachoesophageal fistula (EA/TEF) and also to compare the results with open repair (OR). Subjects and Methods: Patients with EA/TEF who received surgeries in our institution between July 2009 and June 2015 were included in the study. The medical records were retrospectively reviewed. Patients are divided into two groups as follows: TR and OR. Parameters collected includes demographics, operation time, conversion, time to oral feeding, length of hospital stay, complications, and growth status. Statistical Analysis Used: Wilcoxon rank sum test, Chi-square, and Fisher's exact test. Results: A total of 21 patients with EA/TEF, 19 with type C and 2 with type A, were enrolled. There were 9 and 12 patients in TR and OR groups, respectively. There was no significant difference in demographics between both groups. Median operation time was significantly longer in TR (197.5 vs. 115 min, P < 0.01). The operations were converted in the initial three patients. In the following six patients, only one patient with pure EA required conversion. Median time to oral feeding was significantly longer in TR (12 vs. 7 days, P = 0.04). Anastomotic leakage occurred in three and one patients, respectively (33.3% vs. 8.3%, P = 0.27). Esophageal dilatation was required in 3 (33.3%) and 4 (33.3%) patients for esophageal stenosis in TR and OR groups, respectively (P = 0.999). Fundoplication was required in 2 (22.2%) and 3 (25%) patients of TR and OR groups, respectively (P = 1.00). Recurrent TEF developed in one patient (11.1%) of TR. The bodyweight fell behind 3 percentiles of the growth curve in 6 (66.7%) and 6 (50%) patients (P = 0.660). Conclusions: TR for EA/TEF is feasible. The initial experiences revealed longer operation time and higher complication rate compared to OR.